Yi-Shen-Hua-Shi regulates intestinal microbiota dysbiosis and protects against proteinuria in patients with chronic kidney disease: a randomized controlled study - Xingtong Dong; Jialing Zhang; Wen Li; Yinping Li; Linpei Jia; Zhaohui Liu; Wenjing Fu; Aihua Zhang (Taylor & Francis Group, 2024)
AbstractContext Yi-Shen-Hua-Shi (YSHS) is a traditional Chinese medicine that treats chronic kidney disease (CKD). However, its efficacy in reducing proteinuria and underlying mechanisms is unknown.Objective This single-center randomized controlled trial explored whether YSHS could improve proteinuria and modulate the gut microbiota.Materials and methods 120 CKD patients were enrolled and randomized to receive the renin-angiotensin-aldosterone system (RAAS) inhibitor plus YSHS (n = 56) or RAAS inhibitor (n = 47) alone for 4 months, and 103 patients completed the study. We collected baseline and follow-up fecal samples and clinical outcomes from participants. Total bacterial DNA was extracted, and the fecal microbiome was analyzed using bioinformatics.Results Patients in the intervention group had a significantly higher decrease in 24-h proteinuria. After 4 months of the YSHS intervention, the relative abundance of bacteria that have beneficial effects on the body, such as Faecalibacterium, Lachnospiraceae, Lachnoclostridium, and Sutterella increased significantly, while pathogenic bacteria such as the Eggerthella and Clostridium innocuum group decreased. However, we could not find these changes in the control group. Redundancy analysis showed that the decline in 24-h proteinuria during follow-up was significantly correlated with various taxa of gut bacteria, such as Lachnospiraceae and the Lachnoclostridium genus in the YSHS group. KEGG analysis also showed the potential role of YSHS in regulating glycan, lipid, and vitamin metabolism.Discussion and conclusion The YSHS granule reduced proteinuria associated with mitigating intestinal microbiota dysbiosis in CKD patients. The definite mechanisms of YSHS to improve proteinuria need to be further explored.Trial registration ChiCTR2300076136, retrospectively registered.